A solution of concurrent queue on local and distributed Python STM - Popovic, Marko; Kordic, Branislav; Popovic, Miroslav; Basicevic, Ilija (Telfor Journal, 2019)
This paper was motivated by the two open research challenges in the area of STMs. The first challenge is the development of STM based concurrent queues, whereas the second, maybe even greater, challenge is the development of distributed STMs. Python is assumed as a target language. In this paper, four main contributions are made. First, the concurrent queue data structure on the local Python STM is developed. Second, a distributed STM in Python, called Distributed Python STM, is developed. Third, the developed concurrent queue is ported on the Distributed Python STM. Fourth, the developed concurrent queue is verified using unit and system testing. The developed concurrent queue successfully passed all of the unit and the system tests on both local Python STM and Distributed Python STM.